1991
DOI: 10.1063/1.859992
|View full text |Cite
|
Sign up to set email alerts
|

Strong plasma wave excitation by a ‘‘chirped’’ laser beat wave

Abstract: A modification of the plasma beat-wave excitation scheme is proposed, aimed at a significant increase of the resulting plasma wave amplitude. The modification employs two laser beams with a down-chirped beat frequency that follows, on the average, the amplitude-dependent frequency of the intense plasma wave. Numerical and analytical calculations that support the proposed scheme are presented. Also, new analytical solutions for the constant beat-frequency case are obtained. Finally, a plausible experimental set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…It was extensively studied in the context of relativistic particle acceleration: in the 40-ies by McMillan [5], Veksler [6] and Bohm and Foldy [7,8], and more recently [9][10][11][12]. Additional applications include a quasiclassical scheme of excitation of atoms [13] and molecules [14], excitation of nonlinear waves [15,16], solitons [17,18], vortices [19,20] and other collective modes [21] in fluids and plasmas, an autoresonant mechanism of transition to chaos in Hamiltonian systems [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was extensively studied in the context of relativistic particle acceleration: in the 40-ies by McMillan [5], Veksler [6] and Bohm and Foldy [7,8], and more recently [9][10][11][12]. Additional applications include a quasiclassical scheme of excitation of atoms [13] and molecules [14], excitation of nonlinear waves [15,16], solitons [17,18], vortices [19,20] and other collective modes [21] in fluids and plasmas, an autoresonant mechanism of transition to chaos in Hamiltonian systems [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The MP-LWFA concept has been investigated theoretically [40][41][42][43][44][45][46][47][48] but has not previously been demonstrated experimentally. The idea of using a long pulse with temporally non-uniform modulation to overcome the Rosenbluth-Liu limit was proposed, within the context of PBWA, by Deutsch et al [49], who suggested using a pair of frequency-chirped laser pulses.…”
mentioning
confidence: 99%
“…Rosenbluth and Liu [5] demonstrated that this dependency results in the relativistic saturation of the plasma wave amplitude. A number of authors have proposed ways of circumventing the Rosenbluth-Liu limit by detuning [6,7] or chirping [8] the beatwave frequency of long drivers.…”
Section: Introductionmentioning
confidence: 99%